2015
DOI: 10.5038/1827-806x.44.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Cave Cyanobacteria showing antibacterial activity

Abstract: Abstract:al., Engene et al., 2013). These interesting and biochemically active compounds possess biological activity covering a wide range of antibacterial (Mundt et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Considering the last-mentioned approach, caves represent one of the most attractive environments with a strong potential for the discovery of novel antimicrobials. Antimicrobial activity of different cave microorganisms against pathogenic bacteria was reported previously (Herold et al, 2005;Nakaew et al, 2009;Rajput et al, 2012;Cheeptham et al, 2013;Rule & Cheeptham, 2013;Tomova et al, 2013;Lamprinou et al, 2015); a new genus of bacteria, producing antimicrobial substances, was identified in a cave in Thailand (Nakaew et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Considering the last-mentioned approach, caves represent one of the most attractive environments with a strong potential for the discovery of novel antimicrobials. Antimicrobial activity of different cave microorganisms against pathogenic bacteria was reported previously (Herold et al, 2005;Nakaew et al, 2009;Rajput et al, 2012;Cheeptham et al, 2013;Rule & Cheeptham, 2013;Tomova et al, 2013;Lamprinou et al, 2015); a new genus of bacteria, producing antimicrobial substances, was identified in a cave in Thailand (Nakaew et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
“…Antibiotic resistance of pathogenic bacteria became one of the greatest threats to human health over the last few decades (Blair et al, 2015). A few different approaches are used to resolve this problem: chemical synthesis of novel antibiotics (Wright et al, 2014), discovery and development of novel agents capable of circumventing or neutralizing the existing resistance mechanisms (Blair et al, 2015), as well as search for new natural antimicrobials (Lamprinou et al, 2015). Considering the last-mentioned approach, caves represent one of the most attractive environments with a strong potential for the discovery of novel antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Groth & SaizJimenez (1999) have suggested that actinomycetes are abundant in caves and their growth is favoured by the association of low temperature and high relative humidity. Moreover, algae and cyanobacteria have been commonly found in caves (e.g., Banfield et al, 1999;Roldán & Hernández-Mariné, 2009;Lamprinou et al, 2015), whereas Laiz et al, (2000) sampled many bacterial isolates from speleothems, and more specifically from stalactites, which include various species of Streptomyces, Bacillus, Nocardiopsis, Rhodococcus, Agromyces, Arthrobacter, Amycolatopsis, Brevibacillus, Micrococcus, Staphylococcus, Paenibacillus and Variovorax. Therefore, in the microenvironments within stalactites, the metabolic activities of such microorganisms may have locally lowered the pH enough to promote the alteration of muscovite in the Agios Georgios stalactite.…”
Section: Implications For Microbial Muscovite Dissolutionmentioning
confidence: 99%
“…Cyanobacteria are an interesting source of natural bioactive compounds (Chlipala et al 2011) that possess antibacterial (Gantar et al 2011;Lamprinou et al 2015), antimycotic (Swain et al 2017) and anticancer (Kinghorn et al 2016) activity. Terrestrial cyanobacteria, particularly, form an interesting subgroup of previously uninvestigated diversity (Garcia-Pichel et al 2001).…”
Section: Introductionmentioning
confidence: 99%